Long-term effect of photoperiod, temperature and feeding regimes on the respiration rates of Antarctic krill (Euphausia superba) - Brown, M; So Kawaguchi; Candy, S; Yoshida, T; Patti Virtue; Stephen Nicol (2013)
Antarctic krill is thought to undergo an annual cycle of biological processes to cope with seasonal changes in their environment. The question of whether, and to what degree, seasonal environmental parameters such as photoperiod, food availability and temperature govern metabolism in krill is not clear. In this long-term laboratory study, respiration rates were determined in krill incubated under simulated natural light cycle or total darkness, subjected to fed or starved conditions and on krill kept at different temperatures (−1°C, 1°C and 3°C). There was a strong and significant increasing trend of respiration rates with month in all experimental treatments. In August (late winter), the mean respiration rates ranged between 0.22 - 0.35 μL O 2 mg·DW −1 ·hr −1 for krill in both simulated seasonal light and complete darkness, and 0.25 - 0.26 μL O 2 mg·DW −1 ·hr −1 for both fed and starved krill. Mean maximal respiration rates were recorded in October and December for all light and feeding treatments (0.46 - 0.56 μL O 2 mg·DW −1 ·hr −1 ). Mean respiration rates for krill in the temperature treatments ranged between 0.24 - 0.30 μL O 2 mg·DW−1·hr−1 in September reaching mean maximal rates in November and February (0.60 - 0.71 μL O 2 mg·DW −1 ·hr −1 ). The covariate total length of krill was found to be non-significant and there was generally no significant interaction of experimental treatment with month and only for photoperiod comparison was the treatment main effect significant. The dark treatment gave higher respiration rates, and this needs careful interpretation. Results here suggest that, although light, food availability and temperature significantly affect metabolic rates, overall general seasonal pattern of winter low-summer high in respiration observed through the current experiment seemed to have followed an endogenous seasonal rhythm which had already been adjusted to the annual cycle prior to commencement of the experiment.